2019
DOI: 10.1124/jpet.119.257204
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships, Pharmacokinetics, and Pharmacodynamics of the Kir6.2/SUR1-Specific Channel Opener VU0071063

Abstract: Glucose-stimulated insulin secretion from pancreatic b-cells is controlled by ATP-regulated potassium (K ATP) channels composed of Kir6.2 and sulfonylurea receptor 1 (SUR1) subunits. The K ATP channel-opener diazoxide is FDA-approved for treating hyperinsulinism and hypoglycemia but suffers from off-target effects on vascular K ATP channels and other ion channels. The development of more specific openers would provide critically needed tool compounds for probing the therapeutic potential of Kir6.2/SUR1 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Channel activity was measured using a thallium flux assay that reports the inwardly directed movement of thallium into T‐REx‐HEK‐293 cells heterologously expressing Kir6.2/SUR1 (Kharade, Nichols, & Denton, ). As shown in Figure , treatment of T‐REx‐HEK‐293‐Kir6.2/SUR1 cells with the SUR1‐specific activator, VU0071063 (Kharade et al, ; Raphemot et al, ) (positive control), or DCPIB, led to an increase in thallium flux in HEK‐293‐Kir6.2/SUR1 cells. Taken together, these data indicate that DCPIB suppresses mitochondrial respiration and ATP synthesis in HAP‐1 and HEK‐293 cells independently of LRRC8A‐dependent VRAC.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Channel activity was measured using a thallium flux assay that reports the inwardly directed movement of thallium into T‐REx‐HEK‐293 cells heterologously expressing Kir6.2/SUR1 (Kharade, Nichols, & Denton, ). As shown in Figure , treatment of T‐REx‐HEK‐293‐Kir6.2/SUR1 cells with the SUR1‐specific activator, VU0071063 (Kharade et al, ; Raphemot et al, ) (positive control), or DCPIB, led to an increase in thallium flux in HEK‐293‐Kir6.2/SUR1 cells. Taken together, these data indicate that DCPIB suppresses mitochondrial respiration and ATP synthesis in HAP‐1 and HEK‐293 cells independently of LRRC8A‐dependent VRAC.…”
Section: Resultsmentioning
confidence: 92%
“…After 8‐min incubation period, 10 μl/well thallium stimulus buffer (125 mM NaHCO 3 , 1.8 mM CaSO 4 , 1 mM MgSO 4 , 5 mM glucose, 1.8 mM Tl 2 SO 4 , and 10 mM HEPES, pH 7.4) was added and data was collected for another 4 min. VU0071063 (Kharade et al, ; Raphemot et al, ) (positive control) and DCPIB were serially diluted threefold in DMSO and then dissolved in assay buffer to obtain 11‐point CRCs. The data acquisition and analysis were performed using Waveguide (WaveFront Biosciences) and Microsoft excel.…”
Section: Methodsmentioning
confidence: 99%
“…When carbachol was applied together with glucose and diazoxide, TPS was not induced. Since diazoxide does not prevent glucose intake or metabolization (Aizawa et al, 1994;Gembal, Gilon, & Henquin, 1992;Kharade et al, 2019), these data reveal the need for the requirement of membrane depolarization and calcium entry to induce TPS. Tolbutamide, an antidiabetic drug, acts in a manner opposite to diazoxide, blocking ATP-K channels, depolarizing cells, and inducing the opening of calcium channels and insulin secretion even in the absence of glucose.…”
Section: Discussionmentioning
confidence: 94%
“…This same group of investigators identified VU0071063 (IC 50 = 7 µM) as an activator of Kir/SUR1 channels. 86 Importantly, VU0071063 was more potent than the KCO diazoxide in activating the Kir6.2/SUR1 channel and inhibited glucose-dependent insulin release when tested in mouse pancreatic islet cells at a concentration of 10 µM.…”
Section: Ion Flux Analysismentioning
confidence: 94%
“…Opening of Kir channels allows Tl + to enter into the cell and bind to a Tl + -sensitive fluorescent dye, causing a fluorescent signal. In Rb + flux experiments (not shown), Rb + is loaded into the cells and the efflux of Rb + into the supernatant is measured with AAS or a scintillation counter ( 86 Rb + ). ( C ) Electrophysiological methods include the traditional whole-cell patch clamp technique (left panel) and newer APC systems (right panel).…”
Section: Screening Technologies For Kir Channelsmentioning
confidence: 99%